A Mobile Ecotourism Recommendations System Using Cars-Context Aware Approaches - Rosmawarni, Neny; Djatna, Taufik; Nurhadryani, Yani (Journal of Telematics and Informatics, 2013)
The requirements to fullfill mobility of ecotourism activities have been urgent to support each traveler with the mobile gadget application. The objective of this research is to develop an application of recommendation system based on online user personalization. This application provided features to recommendation of ecotourism based on profile user and current location, then supplied information about distance and facilities in each ecotourism place. The main of computation worked online which was based on approach called as CARS (Context Aware Recommender Systems) algorithm. The result showed that the application framework succeeded to give appropriate recommendations and explaination on a mobile platform both in the form of profile based spatial data and user preferences.